Age-Related Differences in the Presentation, Management, and Clinical Outcomes of 100,000 Patients With Venous Thromboembolism in the RIETE Registry - Ortega, Alberto García; Jiménez, David; Pedro-Tudela, Ana; Pérez-Ductor, Cristina; Fernández-Capitán, Carmen; Falgá, Conxita; Skride, Andris; Siniscalchi, Carmine; Weinberg, Ido; Monreal, Manuel (Archivos de bronconeumología, 2024)
INTRODUCTION: Although older adults represent a significant proportion of patients with venous thromboembolism (VTE), the data on the impact of age-related differences in the clinical presentation, management, and outcomes of VTE are scarce. METHODS: We analyzed data from the RIETE registry database, an ongoing global observational registry of patients with objectively confirmed VTE, to compare patient characteristics, clinical presentation, treatments, and outcomes between elderly (≥70 years) vs. non-elderly (<70 years) patients. RESULTS: From January 2001 to March 2021, 100,000 adult patients were enrolled in RIETE. Elderly patients (47.9%) were more frequently women (58.2% vs. 43.5%), more likely had unprovoked VTE (50.5% vs. 45.1%) and most often presented with severe renal failure (10.2% vs. 1.2%) and acute pulmonary embolism (PE) (vs. deep vein thrombosis) (54.3% vs. 44.5%) compared to non-elderly patients (p<0.001 for all comparisons). For the PE subgroup, elderly patients more frequently had non-low risk PE (78.9% vs. 50.7%; p<0.001), respiratory failure (33.9% vs. 21.8%; p<0.001) and myocardial injury (40.0% vs. 26.2%; p<0.001) compared to non-elderly patients. Thrombolysis (0.9% vs. 1.7%; p<0.001) and direct oral anticoagulants (8.8% vs. 11.8%; p<0.001) were less frequently administered to elderly patients. Elderly patients showed a significantly higher 30-day all-cause mortality (adjusted odds ratio [OR] 1.36, 95%CI: 1.22-1.52) and major bleeding (OR, 2.08; 95%CI, 1.85-2.33), but a lower risk of 30-day VTE recurrences (OR, 0.62, 95%CI, 0.54-0.71). CONCLUSIONS: Compared with non-elderly patients, elderly patients had a different VTE clinical profile. Advanced therapies were less frequently used in older patients. Age was an independent predictor of mortality.
Keywords: Recurrence; antikoagulancia; Pulmonary Embolism; Hemorrhage; Aged; senioři; registrace; recidiva; Venous Thromboembolism; krvácení; žilní tromboembolie; lidé; ženské pohlaví; Anticoagulants; Humans; Registries; Female; lidé středního věku; plicní embolie; Middle Aged